Cracked : recovering after traumatic brain injury - Calderwood, Lynsey, 1978- (Jessica Kingsley Pub., 2003)
I didn't even recognize my own face in the mirror. Nothing felt right. Dazed. Paralysed by fear, my first instinct was to run but I had nowhere to hide ... Voices echoed, ricocheting across the room. I wished they sounded familiar.' At the age of 14, Lynsey Calderwood suffered a traumatic brain injury that left her physically unmarked but destroyed her memory. Thrust back into an apparently nonsensical world of which she had no recollection, Lynsey spiralled downwards into depression and eating disorders as she became socially ostracized. This is the story, in her own words, of Lynsey's quest to discover her identity and, eventually, to come to terms with her disability. She faces devastating setbacks and her sense of loss, grief and rage is movingly recalled. Courage and perseverance, coupled with her engaging sense of humour, see her through; and her tale will be an inspiration to anyone who has faced similar obstacles.